Management of the real estate market and housing preferences of students and graduates of UPH in Siedlce - Roman, Kamil; Sawczuk, Damian (Management and Administration Journal, 2019)
The aim of this publication is to learn the preferences of residential Students and Graduates of the University of Natural Sciences and Humanities in Siedlce. The theoretical part of article contains information about behaviors on real estate market. Next, the research part presents the results of surveys and conducted among students and alumni Siedlce University. The main purpose of the article is rating of adjusting Siedlecki real estate market to needs of the students